Pengembangan Media Pembelajaran Interaktif Berbasis Microsoft Power Point Untuk Kelas V Tema 3 Makanan Sehat Subtema 1 di Sekolah Dasar Negeri Giling - Urfi Mutiarohmah Hanggraeni Putri; Joko Sulianto; Fine Reffiane (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The objectives to be achieved in this research are the validity and feasibility of Microsoft PowerPoint for class V Theme 3 Subtheme 1 in Elementary School. This type of research is research development Research and Development (R & D) is a research method used to make a product and test the effectiveness of the product only to a limited trial or only at stage six of the ten steps of the Borg & Gall model, namely Research and information collecting, Planning, Develop preliminary form of product, Preliminary field testing, Main product revision, Main field testing. The subjects of this research are teachers and students of SD Negeri Giling 01. This research is based on the aim of developing interactive learning media based on Microsoft powerpoint that is suitable for use by elementary school students. The research method used is the Borg and Gall method with six steps out of ten research steps. The analysis technique in this study uses observation, interviews, and questionnaire responses. The results of the research, the media tested, is very feasible and efficient to be a learning medium in class V Elementary School.